Investigation of the capital asset pricing model (CAPM) in Singapore - Kang, Yong Wee (2015)
The Capital Asset Pricing Model (CAPM) has been very prevalent on the financial scene in established capital markets. The validity of the model has been widely tested so as to provide a guide for practitioners in their investment decision-making. As for the less advanced capital markets, this validity has not been thoroughly investigated. In the Singapore context, few empirical studies have been done in this field due to the small size and short history of the Singapore stock market. This study attempts to investigate the relevance of various risk measures on the Stock Exchange of Singapore. The data used are monthly returns collected from a sample of ninety-six stocks spanning a period from July 1988 to June 1993. Cross-sectional regression techniques are used to process the data collected in order to examine the validity of the CAPM in Singapore. The end result is an inconclusive stand on the applicability of the CAPM in the local bourse. This result may be due to the various limitations in the study. As the Singapore stock market matures, certain limitations can be overcome and any future research in this field may produce some interesting results.